Comparative Study on the Design of PAD Foundation based on BS8110, EN 1992 and ACI 318 - Victor, Kumala Putra (2018)
This paper presents a comparative study of pad foundation design outcomes based on BS8110, EN 1992 and ACI 318 by using design spreadsheets. This study compares the flexure, shear and punching shear performance, by considering axial load and biaxial moments. The study is focused on some critical input parameters: concrete cover, size of pad foundation and size of column based on a conventional building (residential and commercial). Pad foundation models have been developed by using Autodesk Robot Structural Analysis to verify the flexure and shear. The obtained results compared are leading to some conclusions. For bending performance, EC design requires less area of tensile reinforcement, followed by BS design and ACI design. For share performance, ACI design results in the lowest shear stress, followed by EC design and BS design. For punching shear performance, EC design results in the lowest punching shear stress, followed by BS design and ACI design. For overall performance, EC design provides the most economical design, followed by BS design and ACI design.